A comparison of error‐correction procedures on skill acquisition during discrete‐trial instruction. Issue 2 (24th April 2015) - Carroll, Regina A.; Joachim, Brad T.; St. Peter, Claire C.; Robinson, Nicole
<x xml:space="preserve">Abstract</x> Previous research supports the use of a variety of error‐correction procedures to facilitate skill acquisition during discrete‐trial instruction. We used an adapted alternating treatments design to compare the effects of 4 commonly used error‐correction procedures on skill acquisition for 2 children with attention deficit hyperactivity disorder and 3 children with autism spectrum disorder. For all participants, multiple error‐correction procedures were effective; however, 1 or 2 specific error‐correction procedures led to more efficient skill acquisition for each individual. These results highlight the importance of evaluating the effectiveness and efficiency of error‐correction procedures for individual learners during discrete‐trial instruction. We discuss the use of discrete‐trial instruction with different populations, implications for using multiple measures of procedural efficiency, and several areas for future research.